Analisis Strategi Pelayanan pada Masa Pandemi Covid-19 di Siantar Hotel - Raymondlee Febrianto; Nicholas Marpaung (Regress: Journal of Economics & Management, 2022)
Various strategic steps are certainly implemented in order to provide satisfaction to consumers so that they are satisfied with the services and products of Siantar Hotel which ultimately have an impact on customer loyalty. The purpose of this study was to find out how the service strategy at Siantar Hotel in increasing customer satisfaction during the covid-19 pandemic. This study will discuss the service strategy in increasing Siantar Hotel customer satisfaction during the covid-19 pandemic which focuses on five dimensions of service quality (SERVQUAL). This study uses a qualitative method with a descriptive approach. The location of this research was conducted at the Siantar Hotel, Pematang Siantar city. The subjects in this study were Siantar Hotel President Manager, Siantar Hotel Front Office Supervisor, Siantar Hotel Room Maid and 4 Siantar Hotel consumers. Data collection techniques used are interviews, observation and documentation. Based on the results of the study, it was found that the implementation of service strategies in increasing customer satisfaction in terms of service quality dimensions (SERVQUAL) had been carried out by Siantar Hotel. However, it has not been said to be effective because there are several impacts of the COVID-19 pandemic that must be carefully addressed by obstacle factors which include: regulations for the implementation of restrictions on community activities in the city of Pematang Siantar and cutting employee salaries. The existence of customer satisfaction with the services provided by Siantar Hotel during the covid-19 pandemic can be seen from the customer satisfaction method which consists of several aspects, namely: a system of complaints and customer suggestions and a customer satisfaction survey.